Прогнозування динаміки споживання вторинної пари з випарної установки - Школьна, Олена Валентинівна; Кишенько, Василь Дмитрович; Ладанюк, Анатолій Петрович (НТУ "ХПІ", 2016)
Розглядається метод прогнозування динаміки споживання вторинної пари з випарної установки, що може використовуватись при реалізації випереджувального керування випарною установкою як складовою теплотехнологічного комплексу цукрового заводу. Вибір методу для прогнозування часових рядів, а саме методу нечітких елементарних тенденцій, обґрунтовано та наведено приклад його реалізації в заданій предметній області. Також оцінено адекватність та точність розробленої моделі на основі нечітких елементарних тенденцій в заданій предметній області. Результати досліджень можуть бути використані при реалізації випереджувального керування випарною установкою.

In terms of control the evaporator system as a part of thermal technological complex at the sugar refinery is nonlinear, multidimensional, multiply, complex object. Therefore, the energy efficiency of its operations is advisable to use the methods and approaches to predictive control. For the implementation of predictive control, above all, necessary to solve the problem of time series prediction. The paper presents solved this problem by using a method of analysis and time series forecasting based on fuzzy basic trends. The method proved and an example of its implementation on the basis of time series values of the actuator position on burning steam defecator characterizing the dynamics of consumption of secondary steam from the evaporation unit for a particular customer. As a result, the resulting model for predicting time series based on this method, and assessed its adequacy and accuracy. Determined that the T-model, built by NET capable of successfully and adequately predict fuzzy basic trends and values of the time series position actuator supply second pair of evaporator station on burning defecator, and that the forecasting method can be used in the implementation of advanced control evaporators sugar factory.
Predicting of secondary steam consumption dynamics at the evaporator state
Keywords: прогнозування часових рядів; нечіткі елементарні тенденції; випереджувальне керування; ЧР; НЧР; time series prediction; fuzzy basic trends